Pharmacovigilance study of the association between progestogen and depression based on the FDA adverse event reporting System (FAERS) - Hui Gao; Xiaohan Zhai; Yan Hu; Hang Wu (Scientific Reports)
Abstract Progestogens commonly used in the clinic include levonorgestrel, etonogestrel, medroxyprogesterone, hydroxyprogesterone, progesterone, desogestrel, and megestrol. Progestogens are widely used for contraception and the treatment of endometriosis, threatened abortion and other diseases. However, the correlation between progestogen use and depression is not clear. Therefore, this study used data from the FDA Adverse Event Reporting System (FAERS) database to assess the relationship between progestogen levels and depression. In this study, all data from the first quarter of 2004 to the third quarter of 2024 were extracted and imported into SAS 9.4 software for data cleaning and analysis. The reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN) and Multi-item Gamma Poisson Shrinker (MGPS) were used for Bayesian analysis and disproportionation analysis. Levonorgestrel, medroxyprogesterone, etonogestrel and desogestrel presented positive signals for depression, and medroxyprogesterone also presented positive signals for major depression. Although none of the progestogens presented positive signals for suicide or self-harm, medroxyprogesterone presented a positive signal for suicidal ideation. Conclusion Analysis of data from the FAERS database revealed that levonorgestrel, medroxyprogesterone, etonogestrel, and desogestrel were correlated with depression. These findings provide real-world evidence of the potential risk of progestogen-related depression.